Morphological caste differences and non-sterility of workers in Brachygastra Augusti (Hymenoptera, Vespidae, Epiponini), a neotropical swarm-founding wasp - Baio, Mário V.; Noll, Fernando B. [UNESP]; Zucchi, Ronaldo (New York Entomological Society, 2003)
Morphological caste differences and ovary conditions were analyzed in four colonies of Brachygastra augusti collected in different stages of the colony cycle. Differences between castes are distinct suggesting pre-imaginal determination. Many intermediates (non-inseminated ovary-developed females) were found. Because these intermediate females were morphologically similar to workers, it is suggested that they are young ovary-developed workers. Because there is a more evident overlap between queens and workers in the colony in pre-emergence of workers stage, and in three colonies in latter stages, especially in worker-production colonies, it is suggested that smaller queens are probably less viable than larger queens as observed in previously studied epiponines.
Keywords: Caste differences; Colony cycle; Epiponini; Multivariate analyses; Vespidae